Influence of sucrose on growth and sensitivity of Candida albicans alone and in combination with Enterococcus faecalis and Streptococcus mutans to photodynamic therapy - Tomé, Fernanda Malagutti [UNESP]; Paula Ramos, Lucas De [UNESP]; Freire, Fernanda [UNESP]; Pereira, Cristiane Aparecida [UNESP]; de Oliveira, Ingrid Christine Barbosa [UNESP]; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Oliveira, Luciane Dias de [UNESP] (Springer Nature, 2017)
This study has evaluated the effects of photodynamic inactivation (PDI) using erythrosine as photosensitizer and green light-emitting diode (LED) on biofilms of Candida albicans alone and in combination with Enterococcus faecalis and Streptococcus mutans. We have also evaluated the effect of sucrose on biofilm formation and bacterial growth and sensitivity to PDI. Biofilms were formed in suspension of 106 cells/ml on plates before being grown in broth culture with and without sucrose and incubated for 48 h. Next, the treatment was applied using erythrosine at a concentration of 400 μM for 5 min and green LED (532 ± 10 nm) for 3 min on biofilms alone and in combination. The plates were washed and sonicated to disperse the biofilms, and serial dilutions were carried and aliquots seeded in Sabouraud agar before incubation for 48 h. Next, the colony-forming units per milliliter (CFU/ml; log10) were counted and analyzed statistically (ANOVA, Tukey test, P ≤ 0.05). Results show that S. mutans favors the growth of C. albicans in biofilms with sucrose, with treatment not being effective. However, when the biofilm was grown without sucrose, we found a reduction in biofilm formation and a significant decrease in the PDI treatment (P < 0.0001). In conclusion, both growth and sensitivity to PDI in biofilms of C. albicans are strongly influenced by bacterial combination, and the presence of sucrose affected directly the growth and sensitivity of the biofilm to PDI as sucrose is the substrate for construction of the exopolysaccharide matrix.
Keywords: Biofilm; Candida albicans; Enterococcus faecalis; Photodynamic therapy; Streptococcus mutans; Sucrose